Pengembangan Model Direct Instruction Berbasis Alat Bantu Media Tangan Dalam Pembelajaran Membaca Al-Qur'an Pada Siswa Tunanetra (di seluruh SMA inklusi wilayah X karisidenan Surakarta) - Andriyanto, Fajar, Dr. Moh. Abdul Kholiq Hasan, M.A, M. Ed, Dr. Abdullah Aly, M.Ag (2015)
This study aims to determine the effectiveness of the implementation of direct instruction learning model development based on media tools in the hands of learning to read the Quran on sightless students throughout high school inclusion / equivalent in area X of Surakarta. This study uses Research and Development (R & D). The research data were obtained through observation, interviews, questionnaires, tests, and documentation. The results showed that the model of learning to read the Qur'an whichwere applied in the inclusive high school in area X of Surakarta there is still a lot of deficiencies, either in lesson planning, learning implementation, evaluation of learning, knowledge and enthusiasm of students, services and facilities provided, and the human resources. The results indicated that through the development of direct instruction learning model based on hand media tools which was held across inclusive high school in the area x of Surakarta have showed that the activity of learning to read the Quran on sightless students to become more communicative, attractive, effective and efficient. The third result shows that the ability to read the Qur'an and learning outcomes of students has increased significantly. This was evidenced by the test results of T-test which shows the sig value of 0.000 <0.005, then the Ho is rejected and the Ha is accepted. The comparison of the results of the study showed that students who had passed the grade on the treatment group reaches 6 students (100%). While in the Control group, students who had had passed the grade reaches 4 students (50%) and the other 4 students had not passed the grade with 70 KKM standards. Keywords: learning model; ability; sightless students